Prince of fire - Silva, Daniel, 1960- (New York : G.P. Putnam's Sons, 2005)
Recalled to service in Israel after terrorists steal secrets about his past, art restorer and former spy Gabriel Allon finds himself stalking an elusive master terrorist.
Keywords: Allon, Gabriel (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Intelligence officers -- Fiction; Israelis -- Italy -- Fiction; Art restorers -- Fiction; Bombings -- Fiction; Israel -- Fiction; Italy -- Fiction; Suspense fiction; Spy stories